1978
DOI: 10.1007/bf01981439
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow in male and female rats

Abstract: Sex differences of high significance in the marrow weight relative to femur volume, as well as to body weight, were found in adult rats. A positive significant correlation was found between the femur volume and the marrow volume in both sexes, while a negative significant correlation between femur density and the marrow content (mg/mm3) exists only in male rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies have been reported on the relationships among body weight, bone volume, and bone marrow volume. Skeletal volume was in proportion to body weight in normal dogs [6] and femoral marrow volume was in proportion to bone volume in normal rats [5]. The femoral volume of young rats was reduced to 74% of that of controls by restricted feeding [12] and the tibia length of rats given 33 and 46% restricted feed intakes was 5 and 6-7 % less than that of the controls, respectively…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have been reported on the relationships among body weight, bone volume, and bone marrow volume. Skeletal volume was in proportion to body weight in normal dogs [6] and femoral marrow volume was in proportion to bone volume in normal rats [5]. The femoral volume of young rats was reduced to 74% of that of controls by restricted feeding [12] and the tibia length of rats given 33 and 46% restricted feed intakes was 5 and 6-7 % less than that of the controls, respectively…”
Section: Discussionmentioning
confidence: 95%